Mortality correlates with tree functional traits across a wood density gradient in the Central Amazon - Menezes, Valdiek da Silva; Gimenez, Bruno O.; Wright, Cynthia L.; Higuchi, Niro; Nascimento, Claudete C.; Barros, Fernanda B.; Spanner, Gustavo C.; Rodrigues, Jardel R.; McDowell, Nate; Collins, Adam D.; Negrón-Juárez, Robinson I.; Chambers, Jeffrey Q.; et al. (Frontiers in Plant Science, 2025)
IntroductionUnderstanding the mechanisms of tree mortality in tropical ecosystems remains challenging, in part due to the high diversity of tree species and the inherently stochastic nature of mortality. Plant functional traits offer a mechanistic link between plant physiology and performance, yet their ability to predict growth and mortality remains poorly understood. Given recent increases in tree mortality rates in the Amazon forest following extreme drought and wind events, we tested if lower wood density and acquisitive plant functional traits were associated with increased growth and mortality for common co-occurring trees in the Central Amazon.MethodsSeventeen trees of different species with similar sizes but a range in wood density (WD) and wood traits were felled, then assessed for 27 different individual functional parameters, including whole tree architecture, stem xylem anatomical and hydraulic traits and leaf traits. Traits of the individual trees were related to stand-level growth and mortality rates collected periodically over 30 years from nearby permanent inventory plots.ResultsHigher wood density was associated with smaller leaf size, lower foliar base cations, lower stem water content and sapwood fraction, in agreement with the fast-slow plant economics spectrum. Lower wood density was associated with more acquisitive characteristics with greater hydraulic capacity and foliar nutrient concentrations, correlating with greater growth and mortality rates.DiscussionOur results show that lower wood density is part of a coordinated suite of traits linked to high resource acquisition, fast growth, and increased mortality risk, providing a functional framework for predicting species performance and forest vulnerability under future climate stress.